Pengaruh Pengelolaan dan Peran Badan Usaha Milik Desa (Bumdes) terhadap Peningkatan Perekonomian Desa Paksebali, Kecamatan Dawan, Kabupaten Klungkung - WIRANATA, I KADEK AGUS; DARMAWAN, DWI PUTRA; ARISENA, GEDE MEKSE KORRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
The Influence of Management and Role of Village-Owned Enterprises (Bumdes) on Improving the Economy of Paksebali Village, Dawan District, Klungkung Regency. Paksebali BUMDes is located in Paksebali Village, Dawan District, Klungkung Regency. BUMDes Paksebali has five business units consisting of waste management sites, tourist attractions, savings and loan units, village markets and clean water management. To maximize the performance of BUMDes, of course, it is necessary to know whether Paksebali BUMDes has a positive effect on improving the village economy. This study aims to analyze the characteristics of the Paksebali Village community and to analyze the influence of the management and role of BUMDes on improving the economy of Paksebali Village, Dawan District, Klungkung Regency. The analysis used in this research is descriptive and quantitative analysis using Partial Least Square (PLS). The characteristics of the Paksebali Village community are that the majority of them are of productive age and already have their own income, both working as private employees and entrepreneurs. The management and role of BUMDes has a significant effect on improving the economy of Paksebali Village which can be seen from the absorption of labor, ease of access to capital and an increase in village original income.